2019
DOI: 10.1104/pp.19.01162
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Maintain Acetate Homeostasis by Acetate-Activating Enzymes Impacts Plant Development

Abstract: The metabolic intermediate acetyl-CoA links anabolic and catabolic processes and coordinates metabolism with cellular signaling by influencing protein acetylation. In this study we demonstrate that in Arabidopsis (Arabidopsis thaliana), two distinctly localized acetate-activating enzymes, ACETYL-COA SYNTHETASE (ACS) in plastids and ACETATE NON-UTILIZING1 (ACN1) in peroxisomes, function redundantly to prevent the accumulation of excess acetate. In contrast to the near wild-type morphological and metabolic pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 90 publications
1
35
0
Order By: Relevance
“…Because acetaldehyde showed a completely different labelling pattern compared with acetic acid, we concluded that the biosynthesis of acetic acid in the chloroplast did not involve pyruvate and acetaldehyde, as recently proposed by Fu et al . (2020) and others (e.g. Lin & Oliver, 2008) but needed another biosynthetic origin (point 3; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because acetaldehyde showed a completely different labelling pattern compared with acetic acid, we concluded that the biosynthesis of acetic acid in the chloroplast did not involve pyruvate and acetaldehyde, as recently proposed by Fu et al . (2020) and others (e.g. Lin & Oliver, 2008) but needed another biosynthetic origin (point 3; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A key component of acetate metabolism in plants responsible for the conversion of acetate fermentation products (acetaldehyde, ethanol, and acetate) to acetyl-CoA derived metabolites [ 24 ]. Recently, studies with Arabidopsis double mutants of ACETYL-COA SYNTHETASE (ACS) in plastids and ACETATE NON-UTILIZING1 (ACN1) in peroxisomes (which enables the incorporation of acetate into organic acids and amino acids) showed severe morphological and metabolic phenotypes including delayed growth and sterility associated with hyperaccumulation of cellular acetate and decreased accumulation of acetyl-CoA-derived intermediates of central metabolism [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, identification of acetate esters of phenylpropenes in the leaf essential oils of these species has never been reported in the literature [37,[61][62][63]. Acetic acid is a precursor of acetyl-CoA, which is a metabolic intermediate responsible for the biosynthesis of acetylated metabolites and isoprenoids in plants [64,65]. Hence, we hypothesized that biosynthesis of acetate esters of phenylpropenes is associated with pooling of acetic acid, which is a part of specialized metabolism in P. betle leaves.…”
Section: Hypothesesmentioning
confidence: 97%